2009
DOI: 10.1007/s10995-009-0482-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Paternal Involvement on Feto-Infant Morbidity Among Whites, Blacks and Hispanics

Abstract: Few studies have examined paternal involvement in relation to feto-infant health; therefore we aim to assess the impact of absence of the father on birth outcomes among racial-ethnic subgroups. Florida vital statistics records for singleton births occurring between 1998 and 2005 were used for this study. Births to women less than 20 years of age and births outside the gestational age range of 20-44 weeks were excluded. Adjusted and unadjusted odds ratios and 95% confidence intervals were generated to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 30 publications
5
86
0
2
Order By: Relevance
“…These findings suggest that other critical paternal sociocultural, sociodemographic factors may be at play that could not be assessed because of the limitations of the data set used in this analysis. Previous studies have indicated that an association exists between paternal race/ethnicity (Krishnakumar et al, 2011;Palomar, DeFranco, Lee, Allsworth, & Muglia, 2007), education (Blumenshine, Egerter, Libet, & Braveman, 2011;Bray, Gunnell, & Smith, 2006;Chen et al, 2008;Kiernan, 1997;Saikh et al, 2011), support and involvement (Alio et al, 2011;Alio, Kornosky, Mbah, Marty, & Salihu, 2010;Ghosh, Wilhelm, Dunkel-Schetter, Lombardi, & Ritz, 2010), and alcohol, tobacco, and drug use (Chen et al, 2008;Little & Sing, 1986;Vine, 1996) and adverse feto-infant outcomes. Consequently, it may be beneficial for interconception care, which incorporates prenatal care, to include both mothers and fathers to prevent or minimize health problems for mother and child (Johnson et al, 2006;Mercer et al, 1999;Surkan, Stephansson, Dickman, & Cnattingius, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that other critical paternal sociocultural, sociodemographic factors may be at play that could not be assessed because of the limitations of the data set used in this analysis. Previous studies have indicated that an association exists between paternal race/ethnicity (Krishnakumar et al, 2011;Palomar, DeFranco, Lee, Allsworth, & Muglia, 2007), education (Blumenshine, Egerter, Libet, & Braveman, 2011;Bray, Gunnell, & Smith, 2006;Chen et al, 2008;Kiernan, 1997;Saikh et al, 2011), support and involvement (Alio et al, 2011;Alio, Kornosky, Mbah, Marty, & Salihu, 2010;Ghosh, Wilhelm, Dunkel-Schetter, Lombardi, & Ritz, 2010), and alcohol, tobacco, and drug use (Chen et al, 2008;Little & Sing, 1986;Vine, 1996) and adverse feto-infant outcomes. Consequently, it may be beneficial for interconception care, which incorporates prenatal care, to include both mothers and fathers to prevent or minimize health problems for mother and child (Johnson et al, 2006;Mercer et al, 1999;Surkan, Stephansson, Dickman, & Cnattingius, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This scale has been previously validated among pregnant women in both English and Spanish with good reliability (Cronbach's alpha = 0.89 [English] and 0.94 [Spanish]). 19 Due to the non-normal distribution of responses, we categorized summed responses into groups representing low partner support (score 0-9) and high partner support (score [10][11][12][13][14][15]. For all analyses, women who reported not having a partner (N = 30 Project Viva participants and N = 127 Project ACCESS participants) were categorized as having low partner support (e.g., score = 0).…”
Section: Methodsmentioning
confidence: 99%
“…9 Social support, a construct related to partner support or involvement, is also an important correlate of maternal well-being during pregnancy and perinatal outcomes, including birth weight. 10 Existing research focused on father or partner involvement has generally been limited by several factors: (1) the use of surrogate measures of paternal involvement, such as marital status or the presence of the father's name on the birth certificate as indicative of support [11][12][13][14] ; (2) cross-sectional models that are unable to examine temporal relationships 15 ; and (3) retrospective data that are subject to long-term recall and information bias. 9,16 Furthermore, while there has been some research focus on the relationship between antenatal partner support and women's mental health 17,18 and health behaviors 15 during pregnancy, existing work has focused on a relatively narrow range of pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…9 Besides fathers, mother and child benefit as well when the father is part of the childbearing process. [15][16][17][18]3,4 Supportive fathers during pregnancy can decrease the risk of a preterm delivery by moderating the effects of maternal chronic stress. 15,19 Furthermore, when fathers are involved during the perinatal period, the risk for an infant with a very low birth weight or born very preterm is decreased.…”
Section: Introductionmentioning
confidence: 99%
“…15,19 Furthermore, when fathers are involved during the perinatal period, the risk for an infant with a very low birth weight or born very preterm is decreased. 16 Fathers provide emotional, psychological, and practical help during labour, 3,4 which promotes a more positive childbirth experience for both parents. 17 Sharing this experience stimulates emotional bonding between partners and strengthens the sense of shared responsibility for their child.…”
Section: Introductionmentioning
confidence: 99%